Strategi Sukses E-Commerce: Analisis Pengaruh Pendapatan, Kualitas Pelayanan, dan Kepercayaan Terhadap Minat Beli Masyarakat Melalui Aplikasi Atamtech di Aceh Tamiang - Putri, Riona; Kurlillah, Anis; Ulya , Zikriatul; Yusmami (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This research aims to find out how income, service quality and trust influence people's buying interest through the Atamtech application in Aceh Tamiang. The approach used in this research is quantitative research. The data source used is primary data obtained through a questionnaire with Likert scale measurements with the population in this study being the people of Aceh Tamiang. Samples were taken using random sampling and 250 people were sampled in this study. Data used multiple linear regression methods, descriptive tests, normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests, linearity tests, t tests, f tests, and coefficient of determination tests using SPSS 29.0.2.0 software. Based on the research results, it can be concluded that income (X1) on people's buying interest (Y) partially has a significant influence. Service quality (X2) on people's buying interest (Y) has a significant influence. Trust (X3) on people's buying interest (Y) partially has a significant influence. With an income test reliability value of 0.787, service quality of 0.873, trust of 0.704 and public buying interest of 0.838.